Intrinsic Motivation, Effort and the Call to Public Service - Banuri, Sheheryar; Keefer, Philip (World Bank, Washington, DC, 2014)
Pay schemes in the public sector aim to attract motivated, high-ability applicants. A nascent literature has found positive effects of higher pay on ability and no or slightly positive effects on motivation. This paper revisits this issue with a novel subject pool, students destined for the private and public sectors in Indonesia. The analysis uses dictator games and real effort tasks to examine wage effects on a measure of motivation that exactly matches the mission of the public sector task. The model and experimental design allow for precisely measuring (1) the distribution of ability over the effort task; (2) the distribution of motivational preferences for public sector missions; and (3) outside options when choosing to work for public sector missions. Three novel conclusions emerge. First, more pro-social workers do, in fact, exert higher effort in a pro-social task. Second, in contrast to previous research, motivated individuals are more likely to join the public sector when public sector pay is low than when it is high. Third, real public sector workers exhibit greater pro-sociality than private sector workers, even for entrants into the Indonesian Ministry of Finance.